OPTIMALISASI PERAN MEDIA SOSIAL SEBAGAI MEDIA PEMASARAN UNTUK PRODUK UKM - Rochman, Fatkhur; Zaini, Achmad; Indrianti, Tiitien; Masreviastuti; Waris, Abdul; Arjo, Tri Ramadani (Jurnal Kabar Masyarakat, 2023)
The targets of the activity are residents of Duwet Village, Tumpang District, Malang Regency, East Java, who work as SMEs of processed garden products such as bamboo crafts, banana chips, tomato jam, corn chips, etc. The aim of this activity is to provide training to residents on how to market products by utilizing social media such as WhatsApp and Instagram. So that sales of products that have been produced by residents can have a wider market share, marketing efficiency, and as a means to maximize the social media that residents have not only for sending messages but can be enhanced for more productive things.